2020
DOI: 10.1097/md.0000000000021785
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent cisplatin or cetuximab with radiotherapy in patients with locally advanced head and neck squamous cell carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Our finding is supported by similar data [ 20 , 44 ], which confirmed that toxicity of platinum derivates and cetuximab is comparable. However, other authors have shown that BRT with cetuximab resulted in poorer overall survival, progression-free survival, locoregional control, and distant metastasis-free survival than cisplatin-based therapy [ 11 , 20 , 45 ]. Altogether, these results practically reduce the value of cetuximab in the treatment of advanced HNC, but cetuximab still remains a valuable option for patients with contraindications to platinum-based therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is supported by similar data [ 20 , 44 ], which confirmed that toxicity of platinum derivates and cetuximab is comparable. However, other authors have shown that BRT with cetuximab resulted in poorer overall survival, progression-free survival, locoregional control, and distant metastasis-free survival than cisplatin-based therapy [ 11 , 20 , 45 ]. Altogether, these results practically reduce the value of cetuximab in the treatment of advanced HNC, but cetuximab still remains a valuable option for patients with contraindications to platinum-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment is based on extensive resections followed by concurrent chemoradiotherapy (CRT) with platinum derivatives or concurrent RTH with cetuximab (BRT) or on definitive concurrent chemoradiotherapy in inoperable cases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, monoclonal antibodies such as cetuximab, that blocks EGFR activation, in combination with radiotherapy has been successfully used in the treatment of locoregionally advanced HNSCC, resulting in a better overall survival with low toxicity (Bonner et al, 2010). However, several clinical studies revealed that using cetuximab was detrimental in term of tumor control compared to other chemotherapeutic agents like cisplatin (Mehanna et al, 2019; Tang et al, 2020). It is evident from previous studies that activation of EGFR led to induction of EphB4, suggesting a functional interaction between these two cell membrane receptors (Masood et al, 2006; Park et al, 2015).…”
Section: Eph/ephrin Expression In Hnsccmentioning
confidence: 99%
“…Concurrent chemoradiotherapy is an established therapeutic option for advanced HNSCC [ 4 ]. In randomized trials, concurrent chemo- and radiotherapy improved survival rates [ 5 , 6 ]. These promising results suggest that this combination can enhance local and regional disease control in the head and neck, the most common region of relapse [ 7 ].…”
Section: Introductionmentioning
confidence: 99%